2013
DOI: 10.26719/2013.19.6.527
|View full text |Cite
|
Sign up to set email alerts
|

Oral health behaviours in relation to caries and gingivitis in primary-school children in Tehran, 2008

Abstract: The objectives of this cross-sectional study were to determine the prevalence of caries, severe caries and gingivitis in Tehran primary-school children and to analyse the relationship between children's oral hygiene habits and prevalence of these oral health diseases. Data were collected on the oral hygiene habits of 1271 Tehran schoolchildren (637 boys, 634 girls) aged 9-13 years. Clinical examinations were performed to determine the decayed, missed and filled teeth (DMFT) and the presence of gingivitis. Tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 9 publications
2
14
1
Order By: Relevance
“…All these dissimilarities might expose girls to be more susceptible to dental caries presence than boys. is result agrees with the results of a national study by Jessri et al [13], studies by Heinrich-Weltzien et al [45] in the Philippines and Zhang et al [3] in Hong Kong, and a study by Laganà et al [46] in Albania.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…All these dissimilarities might expose girls to be more susceptible to dental caries presence than boys. is result agrees with the results of a national study by Jessri et al [13], studies by Heinrich-Weltzien et al [45] in the Philippines and Zhang et al [3] in Hong Kong, and a study by Laganà et al [46] in Albania.…”
Section: Discussionsupporting
confidence: 92%
“…According to World Health Organization reports, dental caries affects 60-90% of schoolchildren in both developing and developed countries [11,12]. Furthermore, studies have shown that the prevalence of dental caries was up to 83.3% among Middle-Eastern schoolchildren [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Kaunas a survey have shown that 59.6 % of school children aged 6–8 suffered of light gingivitis [20]. In Tehran it was shown that 87.7 % of schoolchildren aged 9–13 had gingivitis [21]. On the other hand a survey on periodontal status of Greek 12 year’s old population has shown that 41.5 % had bleeding on probing [22].…”
Section: Discussionmentioning
confidence: 99%